Translating organizational change into entrepreneurial identity: A study of energy transition in a large state-owned enterprise - Matteo Landoni (Administrative Sciences, 2023)
This paper presents a proximal study of energy transition in a large state-owned enterprise. Organizational change is the prerequisite for energy transition in a company that has historically understood its own identity in the remunerative oil gas industry. The methodology of the research is a qualitative on-field study of the implementation of the transition strategy inside the company. For this purpose, the research uses primarily first-hand reports collected within the organization in the years 2018-2020. The paper explores the dynamic process of change to reveal the tensions, conflicting identities, and strategies of implementation needed to start the energy transition, shedding light on the formation of a new corporate identity that traces back to the entrepreneurial inception of the company. The role of communication between the different levels of the company was crucial. The management found in the corporate history a moderator of organizational change that led to a renewed entrepreneurial identity. This paper brings evidence that a re-interpretation of the corporate identity is a condition that eases the process of organizational change. The results of the study will provide the theory with a practical case in order to better understand the transitions of state-owned enterprises in their effort to promote organizational change and drive sustainable innovations.
Keywords: 350; energy transition; entrepreneurial identity; organizational change; state-owned enterprise